From Social Media to Learning Media: Developing Valid and Practical TikTok-Based Educational Videos for Stage Makeup Education - Fauziah, Aura; Saputra, Indra (Jurnal Paedagogy, 2026)
This study aims to develop TikTok-based educational video content for stage makeup learning that is valid and practical for vocational high school students majoring in Beauty and Cosmetology. The study employed a Research and Development (R&D) approach using the Four-D (4D) model, which consists of the Define, Design, Develop, and Disseminate stages. The participants included two material experts, two media experts, one language expert, and 39 students who participated in the practicality evaluation. Data were collected using validity and practicality questionnaires based on a five-point Likert scale and were analyzed descriptively. The results indicated that the developed learning media demonstrated high validity, with validity coefficients of 0.955 and 0.833 from the material experts, 0.877 and 0.777 from the media experts, and 0.900 from the language expert, representing valid to highly valid categories. In addition, the practicality evaluation yielded a score of 0.892 (89.16%), indicating that the media was highly practical. These findings demonstrate that the TikTok-based educational video content is valid, practical, and suitable for supporting stage makeup instruction in vocational high schools. The study further suggests that TikTok-based educational videos have considerable potential as digital learning media in vocational education by providing flexible access to practical learning materials, promoting self-directed learning, and accommodating the learning preferences of Generation Z. Accordingly, integrating social media into vocational education can enhance the delivery of practical instruction in the digital learning environment.